Frequency of internet use, economic income, and health of the population-comparative analysis of urban and rural areas based on Chinese General Social Survey - Xifeng Yang (Frontiers Media S.A., 2024)
People's health is one of the important supports for China's economic development. This study uses the 2021 Chinese General Social Survey (CGSS) data to empirically test the impact of residents' Internet use frequency and economic income on residents' health level, and analyzes the differences between urban and rural areas. The empirical test results show that, firstly, the frequency of Internet use can promote the health level of residents, and the promotion effect of Internet use frequency on the health level of rural residents is higher than that of urban residents; Secondly, economic income has a positive promoting effect on the health level of the entire sample of residents, but in urban samples, the regression between economic income and residents' health level is not significant. Third, in the heterogeneity test of region, gender and age, it is found that the impact of residents' Internet use frequency and economic income on residents' health level also has urban-rural differences. Based on this, this study suggests that the government can continue to make efforts to further promote the health level of residents by improving the Internet penetration rate, strengthening the use of Internet skills, carrying out Internet professional skills training and promoting the high-quality development of Internet content.